The occurrence and preference of Botanophila flies (Diptera: Anthomyiidae) for particular species of Epichloë fungi infecting wild grasses - Olszanowski, Ziemowit; Lembicz, Marlena; Górzyńska, Karolina; Michelsen, Verner; Leuchtmann, Adrian (My University, 2013)
Specific associations between species frequently occur in ecological interactions. The aim of this study was to determine the preferences of anthomyiid flies of the genus Botanophila for particular species of fungi as sites for laying eggs and as food for both larvae and adults. The associations of their eggs, larvae and flies with the stromata of different species of Epichloë fungi infecting 7 species of grass in Poland were analyzed. Scanning electron microscopy of the surface of their eggs and an analysis of the genetic sequences of their mitochondrial cytochrome oxidase (COII) were used to identify the taxa of the flies studied. Three types of eggs were distinguished based on their shape, colour and the presence of dorsal folds and sculpturing on the shells. Tentatively,these eggs were assigned to the following species: B. laterella, B. phrenione, B. dissecta and B. lobata. COII sequences obtained from larvae that hatched from two of the types of eggs formed three distinct clades associated with the reference sequences for Botanophila phrenione, B. lobata (new to the fauna of Poland) and a putative species, “Taxon 1”. Only one of these flies (B. lobata) was restricted to a single species of Epichloë (E. bromicola on Elymus repens); B. phrenione was recorded mainly from E. typhina infecting three different species of grass. The results of this study confirm that there is not a close species specific association between this fungus and this insect.
Keywords: Diptera; Anthomyiidae; Botanophila; egg morphology; fungi; Clavicipitaceae; Epichloë; molecular phylogeny; Poland